Floral development in Potamogeton (Potamogetonaceae, Alismatales) with emphasis on gynoecial features - Pereira Nunes, Elaine Lopes [UNESP]; de Lima, Mariana Cortes; de Chiara Moco, Maria Cecilia; Coan, Alessandra Ike [UNESP] (Elsevier B.V., 2012)
The floral developmental patterns and carpel morphologies of Potamogeton illinoensis Morong, P. polygonus Cham. et Schltdl and P. pusillus L were investigated under light (LM) and scanning electron microscopes (SEM) to identify potential characteristics for taxonomic studies. The initiation order of the floral organs was similar in all species; floral phyllotaxy was whorled, with dimerous perigonium and androecium and tetramerous gynoecium. It is suggested that this phyllotactic pattern was acquired by the loss of one organ per whorl, in comparison to the monocots Bauplan. While P. polygonus and P. pusillus showed similar carpel development, P. illinoensis developed its carpels in a unique way, due to a greater growth of the dorsal wall, which positions the carpel opening just above the ovule. Additionally, P. illinoensis may form an extragynoecial compitum. The stigma shape and both the position and shape of the carpel opening were useful to distinguish the three species, and are identified as potential taxonomical characteristics. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ascidiate carpel; Extragynoecial compitum; P. illinoensis; P. polygonus; P. pusillus